I figli dell'Aquila - Pansa, Giampaolo 1935-2020 (Saggi : Storia, 2002)
On the young Fascist militants who chose to fight, in 1943, in the army of the Repubblica sociale italiana (Republic of Salò) of which the eagle was symbol.